Problem Penyusunan Modul Ajar Mata Pelajaran Fikih di Mts Darul Huda Mayak - elga hera wati; Elga hera wati; Erlina Risdiyanti Hapsari; Esa Nindia Rahma; Fakhriza Alien Arwienda; Faris Ardhan Fadillah; Farisa Rofiqul Mahmudah; Nurul Malikah (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The discussion in this research is the difficulty in preparing teaching modules. Teaching modules cannot be implemented properly because teachers have difficulty creating teaching modules. Therefore, this research focuses on teachers' difficulties in compiling teaching modules at middle school. The type of research used is qualitative research. This research was conducted at MTs Darul Huda Mayak Ponorogo which uses the independent curriculum. The data source for this research used interviews with 2 teachers who taught at MTs Darul Huda Mayak Ponorogo. This research instrument uses an interview guide grid and interview sheet. Based on the identification of interview results, there were several teachers who experienced difficulties in compiling teaching modules. The difficulties experienced by the teacher in adapting the material to students' needs, limited understanding of the frequently changing curriculum, limitations in selecting media and effective learning methods.